2004
DOI: 10.1051/0004-6361:20035684
|View full text |Cite
|
Sign up to set email alerts
|

The effect of tidal locking on the magnetospheric and atmospheric evolution of “Hot Jupiters”

Abstract: Abstract. We study the interaction between the planetary magnetosphere and atmosphere of the close-in extrasolar planets HD 209458b and OGLE-TR-56b with the stellar wind during the evolution of their host stars. Recent astrophysical observations of solar-like stars indicate that the radiation and particle environments of young stars are orders of magnitudes larger than for stars with ages comparable to the sun (∼4.6 Gyr). We model the interaction for the present and for early evolutionary stages, showing that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
231
2
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 202 publications
(245 citation statements)
references
References 58 publications
11
231
2
1
Order By: Relevance
“…For a magnetised planet, r c is found by tracing a magnetic field line from the subsolar MP towards the planet. Assuming pressure balance between the solar wind dynamic pressure and the magnetic pressure of the magnetosphere, the standoff distance of the MP can be estimated by Voigt (1981), Grießmeier et al (2004) …”
Section: A1 Magnetic Modelmentioning
confidence: 99%
“…For a magnetised planet, r c is found by tracing a magnetic field line from the subsolar MP towards the planet. Assuming pressure balance between the solar wind dynamic pressure and the magnetic pressure of the magnetosphere, the standoff distance of the MP can be estimated by Voigt (1981), Grießmeier et al (2004) …”
Section: A1 Magnetic Modelmentioning
confidence: 99%
“…These parameters for a Sun-like star can be estimated as a function of the age from the observations discussed above, together with an empirical model for an age-dependence of the solar/stellar wind velocity (Newkirk Jr., 1980;Grießmeier et al, 2004Grießmeier et al, , 2007Lichtenegger et al, 2010) …”
Section: The Time Evolution Of the Solar Windmentioning
confidence: 99%
“…Taking into account that tidal-locking of short periodic exoplanets may result in weaker intrinsic magnetic moments, as compared to fast rotating Jupiter-class exoplanets at larger orbital distances (Grießmeier et al 2004), Khodachenko et al (2007) found that the encountering of dense stellar wind and CME plasma may compress the magnetosphere and force the magnetospheric standoff location to move down to the heights where ionization and ion pick-up of a planetary neutral atmosphere by the CME plasma flow takes place. In our Solar System, it is known that magnetosphere-like structures are found on all planets regardless of whether the planet has an intrinsic global magnetic field or not.…”
Section: Atmospheric Mass Loss Related To Stellar Wind and Cme Inducementioning
confidence: 99%
“…This non-thermal mass loss process depends Article published by EDP Sciences on the strengths of the intrinsic magnetic moments. Grießmeier et al (2004) estimated for slow rotating, tidally locked "Hot Jupiters" that their magnetic moments should be in the range between 0.005-0.1 M Jup . From this study one can expect that weakly magnetized short periodic gas giants, which experience a Venus-like stellar plasma-atmosphere interaction, should exist.…”
Section: Introductionmentioning
confidence: 99%